2009
DOI: 10.1258/jms.2009.008080
|View full text |Cite
|
Sign up to set email alerts
|

Rubella seroprevalence in pregnant women in North Thames: estimates based on newborn screening samples

Abstract: Our findings highlight the need for vaccination to be targeted specifically at migrant women and their families to ensure that they are protected from rubella in pregnancy and its serious consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The incidence of acute hepatitis in Amsterdam was higher among first-generation migrants compared with the Dutch population [26]. In the study conducted to UK-born women [56]. In Germany, 2.2% of 678 newly arrived refugees were seronegative [40].…”
Section: Hepatitis B Virusmentioning
confidence: 88%
See 1 more Smart Citation
“…The incidence of acute hepatitis in Amsterdam was higher among first-generation migrants compared with the Dutch population [26]. In the study conducted to UK-born women [56]. In Germany, 2.2% of 678 newly arrived refugees were seronegative [40].…”
Section: Hepatitis B Virusmentioning
confidence: 88%
“…Studies conducted in Sweden and in the UK showed that migrant women were less likely to be immunized for rubella than native women; in the former group, 10% were found to be seronegative [55,56]. In particular, odd ratios of 4.2 and 5.0 were found for women born in SubSaharan Africa and in South Asia, respectively, compared…”
Section: Measles Mumps and Rubellamentioning
confidence: 96%
“…Unfortunately, our results also revealed a low catch‐up immunisation rate (17.7%) nationwide in women susceptible to rubella. Other studies have demonstrated that immigrant mothers were more likely to be seronegative to rubella, particularly those born in Africa and South Asia 23–25 . To reduce the incidence of congenital rubella in foreign‐born women, since 2002, immigrant women must present proof of rubella immunisation or positive tests for rubella antibodies when applying for temporary and permanent resident status in Taiwan 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Many of these women are likely to have come from rubella-endemic countries, with no or disrupted routine immunisation against rubella. A higher proportion of non-UK-born mothers, particularly those from sub-Saharan Africa and south-east Asia were more likely to be seronegative than UK-born women or white British women [ 23 ], [ 24 ] and analysis of antenatal rubella susceptibility data from London suggested that between 16% and 65% of non-UK-born women were susceptible in 2007 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%